2015
DOI: 10.1097/inf.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age at Antiretroviral Therapy Initiation on Catch-up Growth Within the First 24 Months Among HIV-infected Children in the IeDEA West African Pediatric Cohort

Abstract: Background We described malnutrition and the effect of age at antiretroviral therapy (ART) initiation on catch-up growth over 24 months among HIV-infected children enrolled in the IeDEA West African paediatric cohort (pWADA). Methods Malnutrition was defined at ART initiation (baseline) by a Z-score <-2 SD, according to three anthropometric indicators: Weight-for-age (WAZ) for underweight, Height-for-age (HAZ) for stunting, and Weight-for-Height/BMI-for-age (WHZ/BAZ) for wasting. Kaplan-Meier estimates for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 31 publications
9
40
0
Order By: Relevance
“…In our cohort, late age at ART initiation was strongly associated with stunting and poor HAZ evolution. This finding has been observed in many other studies, but mostly among children younger than age 10 years . Children who spend their first years of life with HIV without ART may have chronic inflammation due to uncontrolled HIV, which can affect growth.…”
Section: Discussionsupporting
confidence: 79%
“…In our cohort, late age at ART initiation was strongly associated with stunting and poor HAZ evolution. This finding has been observed in many other studies, but mostly among children younger than age 10 years . Children who spend their first years of life with HIV without ART may have chronic inflammation due to uncontrolled HIV, which can affect growth.…”
Section: Discussionsupporting
confidence: 79%
“…Finally, even if all HIV-infected children presented a nutritional recovery with ART, with a significant gain in weight and height, the nutritional status was not completely restored for a significant number of children who remained malnourished, even after 1 to 2 years of treatment [24,31,33,34,38,41,47,51]. Thus, ART alone is not sufficient and specific interventions are needed to improve the nutritional care of HIV-infected children.…”
Section: Antiretroviral Treatment and Nutritional Status In Childrenmentioning
confidence: 84%
“…Finally, the age at which ART is initiated in a child may influence the nutritional response. Many authors focusing on this issue have reported that the earlier the treatment was initiated in children, the better was the nutritional response in weight [32,33,37,38,41,42,47] and height [38,42,47,48]. However, some authors reported no effect of age on the nutritional response to treatment [31,45] or even a lower growth in younger children [32].…”
Section: Antiretroviral Treatment and Nutritional Status In Childrenmentioning
confidence: 92%
“…Previous studies consistently describe improved weight outcomes for younger children , possibly related to less severe gastrointestinal impairment and shorter duration of chronic immune activation . Reports on the impact of age on height differ between studies, with improved height outcomes with younger age in some studies , while others reported no difference or worse height outcomes for younger children . HIV‐infected children are increasingly reaching adulthood due to the availability of ART; therefore, studies to evaluate the impact of age at ART initiation on the timing and magnitude of the pubertal growth spurt and final adult height are needed.…”
Section: Discussionmentioning
confidence: 99%